MEDIA MIND MAP DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Saeful Anam; Nikmatuz Zahroh (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2022)
The purpose of this study was to determine whether there are differences in the use of online-based mind media with other online-based visual media on problem-solving abilities, to find out the difference between high parental attention and low parental attention, and to find out the relationship between mind map media and parental attention. both high and low on the problem-solving ability of students at MTs Nurul Huda Leran Manyar Gresik. This study uses a quantitative experimental method using a True Experimental Design, with a Post-Test Only Control Design. This design uses 2 groups, namely the experimental group and the control group. The population of all students was 206, the researcher chose 2 classes, class VIII A as the control class and VIII B as the experimental class. Data collection techniques in the form of questionnaires, tests, and documentation. The data analysis technique used the T-test. From the results of the analysis of hypothesis testing, conclusions can be drawn, 1) it can be seen from the output results using SPSS version 21 using the "Independent Sample T-Test" it is known that the value of Asymp.Sig. (2-tailed) of 0.001 <0.05, it can be concluded that Ha is accepted and Ho is rejected. Thus it can be said. that there is a difference in problem-solving abilities between using mind maps and using visual media. 2) based on the SPSS output "Independent Sample T-Test" it is known that the value of Asymp.Sig. (2-tailed) of 0.034 <0.05, it can be concluded that Ha is accepted and Ho is rejected. Thus it can be said "that there is a difference in problem-solving abilities between high parental attention and low parental attention.